2009
DOI: 10.1111/j.1365-2133.2008.08863.x
|View full text |Cite
|
Sign up to set email alerts
|

Economic evaluation of etanercept in the management of chronic plaque psoriasis

Abstract: This model found the licensed dose regimen of etanercept 50 mg biw to be cost effective in the U.K. This regimen was particularly appropriate for patients with severe disease or poor quality of life at baseline.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 15 publications
0
41
0
Order By: Relevance
“…Other studies have modeled etanercept treatment in psoriasis [25,[46][47][48]. The York model previously mentioned estimated an ICER for intermittent etanercept 25 mg twice daily of £14,460 (approximately €21,690) compared with non-systemic standard of care.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have modeled etanercept treatment in psoriasis [25,[46][47][48]. The York model previously mentioned estimated an ICER for intermittent etanercept 25 mg twice daily of £14,460 (approximately €21,690) compared with non-systemic standard of care.…”
Section: Discussionmentioning
confidence: 99%
“…Following British guidelines, the York model excluded indirect costs. The results of a UK-based economic model comparing etanercept 50 mg twice weekly with non-systemic therapy found the ICER to be £6,217 over a 10 years time horizon [46]. Again this model excluded patients with moderate disease and indirect costs.…”
Section: Discussionmentioning
confidence: 99%
“…The values or changes in utility were measured by levels of PASI response in five studies [24,40,51,53,62]. Three studies mapped the Dermatology Life Quality Index (DLQI) to European Quality of Life-5 Dimensions (EQ-5D) utilities [35,57,59]; however, Woolacott et al [67] mapped the change in DLQI associated with different PASI response categories and baseline DLQI scores to changes in EQ-5D utility. The remaining studies either estimated utility values directly from study patients [22,26,58], stated utility values from previous studies were used without providing further details [43,56], or obtained utilities by response status defined by neither PASI nor DLQI from previous studies [60].…”
Section: Synthesis Of Cost-effectiveness Analysis Studiesmentioning
confidence: 99%
“…Over 90 % of the studies reported objectives (item 1), sources of variable estimates (item 3), methodology of data abstraction (item 7), primary outcome measures (items 10 and 11), and choice of economic model (item 13) ( Table 1). Only five studies conducted a subgroup analysis (item 4), either based on the patients with different disease severity levels at baseline [43,56,59,67] or among patients who completed the study [65]. Approximately 40 % of the studies only estimated the cost-effectiveness ratios (e.g.…”
Section: Quality Assessmentmentioning
confidence: 99%
See 1 more Smart Citation